A review on global threat corona virus disease: COVID-19 - Barbhuiya, Samia begam; Vicky Bareh; Caroline Malsawmtluangi; Parikshit Das (Creative Pharma Assent, 2020)
Corona virus disease is a kind of viral disease caused by Severe Acute Respiratory Syndrome- CoV 2, which is first witnessed in Wuhan city, China and it can be transmit from human to human. Coronavirus size ranges from (65-125 nm) in diameter and contain a single stranded RNA as nucleic acid material, size ranging from 26 to 32 kbps in length. The sub group of coronaviruses family is Alpha (α) Beta (β) Gama (γ) and delta (δ) coronavirus. Coronavirus disease is a kind of respiratory disease which mainly affects the lower respiratory tract of human body. Initially interferon α normalisation, broad spectrum antibiotic and antiviral drugs was used to reduce the viral load. There may be different kind of mode of transmission of this virus for example Respiratory transmission, Aerosol transmission, Contact transmission and Hospital acquired transmission. There is a well explained safety measures is provided to inhibit the COVID-19 spread which should be followed properly. There are some testing processes also developed to determine the presence of this virus. Till now not even a single vaccine is developed for the treatment of this COVID-19 but more than 12 countries across the globe are undergoing trial for more than 150 vaccine candidates.